An outcome and cost analysis of anal fistula plug insertion vs endorectal advancement flap for complex anal fistulae. (July 2015) - Fisher, O. M.; Raptis, D. A.; Vetter, D.; Novak, A.; Dindo, D.; Hahnloser, D.; Clavien, P.‐A.; Nocito, A.
Abstract Aim The study aimed to compare the rate of success and cost of anal fistula plug (AFP) insertion and endorectal advancement flap (ERAF) for anal fistula. Method Patients receiving an AFP or ERAF for a complex single fistula tract, defined as involving more than a third of the longitudinal length of of the anal sphincter, were registered in a prospective database. A regression analysis was performed of factors predicting recurrence and contributing to cost. Results Seventy‐one patients (AFP 31, ERAF 40) were analysed. Twelve (39%) recurrences occurred in the AFP and 17 (43%) in the ERAF group (P = 1.00). The median length of stay was 1.23 and 2.0 days (P < 0.001), respectively, and the mean cost of treatment was €5439 ± €2629 and €7957 ± €5905 (P = 0.021), respectively. On multivariable analysis, postoperative complications, underlying inflammatory bowel disease and fistula recurring after previous treatment were independent predictors of de novo recurrence. It also showed that length of hospital stay ≤ 1 day to be the most significant independent contributor to lower cost (P = 0.023). Conclusion Anal fistula plug and ERAF were equally effective in treating fistula‐in‐ano, but AFP has a mean cost saving of €2518 per procedure compared with ERAF. The higher cost for ERAF is due to a longer median length of stay.